[Carved Spoon] - Antoine, Kobe, (1999- ) (Artist) (2018)
Alder spoon with black trim and abalone inlay on handle. FDSNCA Graduate 2018. Lake Babine Nation. Copyright held by artist. Photograph by Highlight Studio.